Management of chronic osteomyelitis with extra oral fistula in the mandible: Penatalaksanaan osteomielitis kronis disertai fistula ekstraoral pada mandibula - Faisal; M. Irfan Rasul; Eka Prasetiawaty (Makassar Dental Journal PDGI Makassar, 2020)
Background: Osteomyelitis is an inflammation of bone marrow, caused by microorganisms, developed from odontogenic infection, and usually also affects the cortical bone and periosteum. There are several classifications of the osteomyelitis, according to the affected anatomy, acute and chronic, suppurative and non-suppurative. The treatment of the osteomyelitis is surgery and antibiotic therapy. Objective: A case report of a management of chronic osteomyelitis came from odontogenic infection. Case: A-39-years old male patient who came to the hospital, presented complaining of pain and swelling of the right mandibular region for 1 year. From the dental history, tooth on the right lower jaw had been extracted about two years ago. Osteomyelitis had developed from odontogenic infection. On examination, there was an asymmetrical face, right-sided facial swelling and an extraoral fistula, edentulous at 46 and 47 regions. Panoramic radiograph showed radiolucent regions which surround aportion of dense bone. Management: The treatment were sequstrectomy and fistulectomy which performed under general anesthesia. Conclusion: A sequestrectomy is a surgical intervention in treatment of the chronic osteomyelitis to remove the necrotic bone, improve the blood supply in the involved area thereby allowing adequate penetration of antibiotic.